HUBUNGAN KONDISI LINGKUNGAN RUMAH TERHADAP RISIKO JATUH PADA LANSIA - Leni Wijaya; Rissa Dwi Agustin (LPPM STIKes Mitra Adiguna, 2026)
The risk of falls among older adults increases with advancing age and is influenced by various intrinsic and extrinsic factors. Environmental conditions are one of the important extrinsic factors contributing to fall risk in the elderly. Globally, approximately 684,000 deaths are reported each year due to falls. This study aimed to determine the relationship between home environmental conditions and the risk of falls among older adults. This study employed an analytic survey design with a cross-sectional approach. The study population consisted of all members who attended and participated in the Chronic Disease Management Program (Prolanis) at Klinik Pratama 3F Prabumulih, totaling 47 individuals. A purposive sampling technique was used to select 28 respondents who met the inclusion and exclusion criteria. Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses with the Chi-Square test. The univariate analysis showed that 14 respondents (50.0%) had a moderate risk of falls, 10 respondents (35.7%) had no risk of falls, and 4 respondents (14.3%) had a high risk of falls. Unsafe home environmental conditions were identified in 18 respondents (64.3%), while 10 respondents (35.7%) lived in safe environments. The bivariate analysis revealed a p-value of 0.014 (p ? 0.05), indicating a significant relationship between home environmental conditions and fall risk among older adults. This study is expected to provide valuable information and enhance family awareness regarding safe home environment standards to reduce fall risk and prevent fatal outcomes among the elderly.